Window Assembly
Patent Information
- Application Number
- JP2023149390
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2017-07-28
- Filing Date
- 2023-09-14
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2038-07-27
AI Technical Summary
【0030】 本発明の上記および他の利点は、添付の図面に照らして考慮すると、以下の詳細な説明 から当業者に容易に明らかになるであろう。
Smart Images

Figure 0007629965000002 
Figure 0007629965000003 
Figure 0007629965000004
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application is the subject of Ser. No. 62 / 538,167 under 35 U.S.C. 119(e). , which claims the benefit of U.S. provisional patent application filed on July 28, 2017, The entire disclosure is incorporated herein by reference. [Background technology]
[0002] The present invention relates to a window assembly. More particularly, the present invention relates to a window assembly for use in a vehicle. Regarding assembly.
[0003] Vehicle windows are a prominent feature of the vehicle's overall design. Among other important functions, Vehicle windows control solar heat gain into the vehicle that occurs in hot climates and keep vehicle occupants cool on the road. It helps protect against debris from the windows. It also improves appearance and provides, for example, solar control and impact resistance for the windows mentioned above. There is often a balance that must be achieved between functionality and performance properties.
[0004] Can be used as a vehicle windshield or separate window, has a pleasant appearance and is lightweight It is therefore desirable to provide a window assembly that has excellent solar control properties and is highly impact resistant. I wish. Summary of the Invention
[0005] An embodiment of the window assembly is described below. In one embodiment, the window assembly includes a first The first glass plate is chemically strengthened and has a surface pressure of 400 MPa or more. A second glass sheet is provided having a first major surface and a second major surface. The second main surface of the second glass plate and the first main surface of the first glass plate are opposed to each other. The plate is made of 68-74% by weight of SiO2, 2-6% by weight of MgO, and 1-10% by weight of CaO. , 12-16 wt% Na2O, 0-1 wt% K2O, 0.8-2.0 wt% Fe2 O3 (total iron), 0-1.25 wt% TiO2, and 0-1.25 wt% CeO2 The polymer interlayer is provided between the first glass sheet and the second glass sheet. The assembly is based on a relative solar radiation spectrum distribution of less than 55% of the air mass 1.5 in the wavelength range of 30 Direct solar transmittance integrated from 0 to 2500 nm, and 65% or more of air mass 1.5 According to the relative solar radiation spectrum distribution below, integrated over the wavelength range 300-2500 nm Indicates the total solar transmittance.
[0006] Preferably, the first glass pane is the inner glass pane.
[0007] Preferably, the first glass pane is a sheet of float glass.
[0008] Preferably, the first glass sheet exhibits a surface compressive stress of 450 MPa or more.
[0009] Preferably, the first glass sheet exhibits a surface compressive stress of 600 MPa or more.
[0010] Preferably, the first glass plate exhibits a surface compressive stress of 600 to 1,000 MPa.
[0011] Preferably, the second glass pane is the outer glass pane.
[0012] Preferably, the second glass pane is a sheet of float glass.
[0013] Preferably, the thickness of the second glass sheet is greater than the thickness of the first glass sheet, more preferably Typically, the thickness of the second glass sheet is at least 1.5 times greater than the thickness of the first glass sheet.
[0014] Preferably, the thickness of the second glass sheet is 4 mm or less, and the thickness of the first glass sheet is It is less than 2mm.
[0015] Preferably, the second glass sheet has 0.8 to 1.9 wt. % Fe2O3 (total iron), more preferably Preferably, 0.9 to 1.9 wt. % Fe2O3 (total iron), and even more preferably, 0.9 to 1 Contains .4% Fe2O3 (total iron) by weight.
[0016] Preferably, the second glass plate contains 0.01 to 0.3 wt % of TiO2.
[0017] Preferably, the second glass sheet is substantially free of Co3O4.
[0018] Preferably, the first glass sheet comprises Al2O3.
[0019] Preferably, the second glass sheet comprises Al2O3.
[0020] Preferably, the second glass plate contains 0 to 2% by weight of Al2O3.
[0021] Preferably, the weight percent of Al2O3 in the second glass sheet is about 1 / 2 the weight percent of Al2O3 in the first glass sheet. It is less than 3% by weight.
[0022] Preferably, the window assembly has a glazing area of 70% or more, measured from the side facing the first glass sheet. Shows total visible light transmittance (illuminant A, 2-degree observer).
[0023] Preferably, the transmitted color exhibited by the window assembly (illuminant D65, 10 degree observer) is , green-yellow.
[0024] Preferably, the transmitted color exhibited by the window assembly (illuminant D65, 10 degree observer) is , a* values from -12 to -5 and ab* values from 0 to 6.
[0025] Preferably, the window assembly has a thickness of less than 5.0 mm. The thickness of the assembly is 2.0 to 5.0 mm.
[0026] In some embodiments, the first glass sheet is made of 66-72% by weight SiO2, 8- 15% by weight MgO, 1-8% by weight CaO, 12-16% by weight Na2O, 0-1% by weight % K2O, and 1.0 to 5.0% Al2O3 by weight. The steel plate contains 4.0 to 5.0% by weight of Al2O3.
[0027] In some embodiments, the first glass sheet is made of 58-70% by weight SiO2, 4- 10% by weight MgO, 0-1% by weight CaO, 12-18% by weight Na2O, 0.1-5 % by weight of K2O, and 5-15% by weight of Al2O3.
[0028] In some embodiments, the window assembly exhibits a direct solar transmittance of 52% or less. Preferably, the window assembly exhibits a direct solar transmittance of between 40 and 55%.
[0029] In some embodiments, the window assembly exhibits a total solar transmittance of 62% or less. Preferably, the window assembly exhibits a total solar transmittance of 55-65%. [Brief description of the drawings]
[0030] These and other advantages of the present invention are best understood from the following detailed description when considered in light of the accompanying drawings, in which: It will be readily apparent to one skilled in the art.
[0031] [Figure 1] 1 is a partial perspective view of a vehicle showing a window assembly according to the present invention; [Diagram 2] FIG. 2 is a front view of the window assembly of FIG. 1. [Diagram 3] FIG. 3 is a cross-sectional view of a portion of the window of FIG. 2 taken along line 3-3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0032] The present invention contemplates various alternative orientations and It is understood that a sequence of steps may be envisaged, as shown in the accompanying drawings: The specific articles, assemblies, and features described in the following specification are intended to be illustrative, but are not to be construed as limiting the scope of the present invention. It should also be understood that the disclosed embodiments are exemplary embodiments. Specific dimensions, orientations, or other physical characteristics shown are limiting unless otherwise noted. Although this may not be the case, various aspects of the present disclosure should not be construed as limiting the scope of the present disclosure. Like elements in the embodiments are generally referred to by like reference numbers within this section of the application. It is possible.
[0033] A window assembly 10 is shown in Figures 1-3. The window assembly 10 is shown in Figure 1. The assemblies described herein are described in relation to a vehicle 12. It should be understood by those skilled in the art that the present invention may have application in off-highway vehicles. Those skilled in the art will appreciate that the present invention may have industrial, locomotive, naval, aerospace, and other applications. You will understand.
[0034] Preferably, the window assembly 10 is a windshield or windscreen window for a vehicle 12. The window assembly is installed in a body opening 14 of the vehicle 12 so as to be 10 is connected to another vehicle body opening in the vehicle 12, such as a side or rear opening of the vehicle 12. It should be understood that in these embodiments (not shown), the window assembly may be The assembly may be a backlight or sidelight for a vehicle. In the present invention, the window assembly may be utilized in another body opening of the vehicle. For example, 10 may be installed in an opening in the roof of a vehicle 12. In this embodiment, the window assembly 10 is a roof light for a vehicle 12 .
[0035] The window assembly 10 includes an inner glass pane 16. The inner glass pane 16 is a window pane as described herein. The inner glass sheet 16 is sometimes called the first glass sheet in the The glass may be formed using a manufacturing process and provided as a sheet of glass. As best seen, the inner glass sheet 16 has a first major surface 18 and a second major surface 20. Preferably, the first major surface 18 and the second major surface 20 are provided in a parallel relationship to one another. In some embodiments, the first major surface 18 is a major surface of the outer glass sheet 22. 26. In these embodiments, when the window assembly 10 is installed A second major surface 20 of the inner glass pane 16 may face the passenger compartment of the vehicle 12 .
[0036] Preferably, the inner glass pane 16 is clear soda-lime-silica glass. In one embodiment, the inner glass pane 16 has a low iron content, which results in high visible light For example, the inner glass plate 16 may contain up to 0.15% by weight of Fe2O3. As used herein, the phrase "total iron" refers to the presence of iron in the glass. Refers to the total weight of iron oxide (FeO+Fe2O3) contained. More preferably, the inner glass Plate 16 should preferably contain no more than 0.1 wt. % Fe2O3 (total iron), and even more preferably no more than 0.02 wt. % Fe2O3 (total iron) or less. In one embodiment, the inner glass pane 16 contains 0. 012% by weight Fe2O3 (total iron). In these embodiments, the inner glass sheet 16 has a color gamut of 91% or higher in the CIELAB color scale system (illuminant A, 2 degree observer) The total visible light transmittance may be indicated.
[0037] In another embodiment, the inner glass sheet 16 is made of 58-72% by weight SiO2, 4-1 5% by weight MgO, 0-8% by weight CaO, 12-18% by weight Na2O, and 0-5 In these embodiments, the inner glass pane 16 contains 1.0 wt. % K2O. % or more of alumina (Al2O3), and 0 to 0.3 mass percent of SO In one such embodiment, the inner glass pane 16 may also have a thickness of 66 to 72 mm. % by weight of SiO2, 8-15% by weight of MgO, 1-8% by weight of CaO, 12-16% by weight % Na2O, and 0 to 1 wt. % K2O. In this embodiment, the inner glass Plate 16 has greater than or equal to 1.0% by weight Al2O3 but less than 5.0% by weight. In this embodiment, the inner glass plate 16 is made of 4.0 to 5.0% by weight of Al2O3. In another embodiment, the inner glass sheet 16 has 5.0 wt. % or more of AlO In this embodiment, the inner glass sheet 16 may have 5 to 15% by weight of A. In this embodiment, the inner glass sheet 16 may also have a thickness of 58 to 70 μm. 0% by weight SiO2, 4-10% by weight MgO, 0-1% by weight CaO, 12-18% by weight % Na2O, and 0.1 to 5 wt. % K2O. In some cases, it may be preferred that the composition of the inner glass sheet 16 be boron-free. In an embodiment, the inner glass pane 16 may be clear float glass. In the embodiment, the transparent float glass is glass according to BS EN572-1 and BS EN57 2-2 (2012). In an embodiment, the inner glass sheet 16 is of another composition, such as a borosilicate composition. It is also possible.
[0038] It is preferred that the inner glass sheet 16 be relatively thin in comparison to the thickness of the outer glass sheet 22. In one embodiment, the inner glass pane 16 has a thickness of 2 millimeters (mm) or less. Preferably, the inner glass sheet 16 has a thickness of 1 mm or less. In the above, the inner glass plate 16 has a thickness of 0.5 to 1.0 mm. The inner glass sheet 16 has a thickness of 0.5 to 0.8 mm. This helps reduce the weight of the window assembly 10, which may improve the fuel economy of the vehicle. , or improving the range of the vehicle if it is an electric vehicle.
[0039] Since the inner glass pane 16 is thin, the window assembly 10 still exhibits a desired amount of impact resistance. To achieve this, the inner glass pane 16 is preferably chemically strengthened. The chemical strengthening processes described herein are suitable for use with the inner glass pane 16. The chemical strengthening process is of the ion exchange type and is carried out using molten salts. In such an embodiment, the sodium ions in the glass are replaced by sodium ions. In this embodiment, the cation is substituted with a monovalent cation having an ionic radius larger than the ionic radius of the cation. In the above, the monovalent cation is, for example, a molten salt of potassium nitrate or a molten salt of potassium nitrate and nitrate. The potassium ions may be provided by a mixture of sodium and potassium hydroxide. Chemically strengthened glass suitable for use as plate 16 is manufactured and sold by Nippon Sheet Glass Co., Ltd. However, other glass sheets are also available. Chemically strengthened glass is also suitable for use as the inner glass pane 16 .
[0040] After chemical strengthening, the inner glass pane 16 preferably exhibits a high surface compressive stress. In this embodiment, the inner glass sheet 16 exhibits a surface compressive stress of 400 MPa or more. In the embodiment, the inner glass sheet 16 exhibits a surface compressive stress of 450 MPa or more. In another embodiment, the inner glass sheet 16 exhibits a surface compressive stress of 600 MPa or more. In these embodiments, the inner glass sheet 16 has a surface resistance of 600 to 1,000 MPa. Preferably, the inner glass sheet 16 has a surface stress of 600 to 800 MPa. More preferably, the inner glass plate 16 has a surface compressive stress of 700 to 800 MPa. In the embodiments described herein, the surface compressive stress is represented by the Strainopt ics Laser GASP-CS(http: / / www.strainoptic s.com / files / Laser%20GASP-CS%20Quick-Star t%20(English).pdf or http: / / www.strainopt ics.com / wp-content / uploads / 2017 / 10 / 2017- This can be measured using the GASP-CS-Quick-Start.pdf. The equipment is from Strainoptics, Inc., 108 W. Montgomery Avenue, North Wales, PA 19454 USA The high strength typically found in chemically strengthened and fully heat-strengthened sodium silicate glasses For surface compressive stress at the level, a Differential Stress Refractometer (DSR) is used to measure the surface compressive stress It is known in the art that such instruments can be used. entific Corporation,3650 Jarvis Avenue,S Kokie, Illinois 60076 USA.
[0041] In certain embodiments, the depth of ion penetration is greater than or equal to 200 microns after chemical strengthening. In another embodiment, after chemical strengthening, the inner glass sheet 16 may also have a thickness of 15 μm. The compressive stress layer may include a compressive stress layer having a depth of 15 to 40 μm or more. More preferably, the compressive stress layer has a depth of 15 to 25 μm. In the embodiment, the inner glass plate 16 has a strength of 550 kgf / mm after chemical strengthening. 2 More than Indicates the Kerr hardness.
[0042] The window assembly 10 also includes an outer glass pane 22. The outer glass pane 22 is a glass pane having a thickness of 100 nm to 150 nm. The outer glass sheet 22 is sometimes called the second glass sheet in the It may be formed using a manufacturing process and provided as a sheet of float glass. As best seen in FIG. 3, the outer glass sheet 22 has a first major surface 24 and a second major surface 25. The first major surface 24 and the second major surface 26 are provided in a parallel relationship to one another. The second major surface 26 of the outer glass sheet 22 and the first major surface 26 of the inner glass sheet 16 18 are opposed and may in certain embodiments be in parallel relationship to one another. In an embodiment (not shown), the window assembly 10 may be configured to accommodate, for example, a head-up display. The second major surface 26 of the outer glass sheet 22 and the The first major surfaces 18 of the inner glass sheets 16 are not provided in parallel relationship to one another. In the embodiment, the second major surface 26 of the outer glass pane 22 or the first major surface 26 of the inner glass pane 16 One major surface 18 may be arranged such that one surface 18, 26 is disposed at an angle relative to the other. do.
[0043] The composition and thickness of the outer glass pane 22 is determined to provide a window that is compatible with the particular solar, visible, and infrared (UV) illumination requirements for which the window assembly 10 is intended. The outer glass pane is selected to exhibit light transmittance and color characteristics. The thickness of 22 is preferably greater than the thickness of the inner glass sheet 16. By providing an outer glass sheet 22 having a thickness greater than that of the glass sheet 16 , the impact resistance of the window assembly 10 is improved as compared to a window assembly having glass sheets of the same thickness. In one embodiment, the outer glass pane 22 is thicker than the inner glass pane 16. In another embodiment, the outer glass sheet 2 has a thickness at least 1.5 times greater than that of the outer glass sheet 2. 2 has a thickness at least 2.0 times greater than the thickness of the inner glass sheet 16. In an embodiment, the outer glass pane 22 has a thickness of 4 mm or less. In one embodiment, the outer glass plate 22 has a thickness of 1.0 to 4.0 mm. In this embodiment, the outer glass plate 22 has a thickness of 1.0 to 3.0 mm. In an embodiment, the outer glass plate 22 has a thickness of 1.2 to 2.5 mm. In some embodiments, the outer glass plate 22 has a thickness of 1.8 to 3.1 mm. Yes.
[0044] Preferably, the outer glass pane 22 is soda-lime-silica glass. The outer glass pane 22 may be made of another composition, such as, for example, a borosilicate or aluminosilicate composition. It is also preferred that the outer glass pane 22 is tinted. In one such embodiment, the outer glass pane 22 is green-yellow. The color may vary depending on the embodiment of the window assembly 10.
[0045] To provide a soda-lime-silica glass having the desired color, the outer glass panes 22 are 68-74% by weight of SiO2, 2-6% by weight of MgO, 1-10% by weight of CaO, 12- 16% by weight Na2O, and 0-1% by weight K2O. The CaO content in the outer glass plate is 1 to 9% by weight, and may be 1 to 8% by weight. In one such embodiment, the CaO in the outer glass sheet 22 is 6 to 8 wt. %. The outer glass plate 22 may contain 0 to 2% by weight of Al2O3. If it is desired to improve the chemical durability of the outer glass pane, the outer glass pane 22 may be coated with 1 to 20% water. 2% by weight of Al2O3. Thus, in one particular embodiment, the outer The composition of the first glass pane 22 contains less Al2O3 than the composition of the inner glass pane 16.
[0046] Additionally, the desired amount of total iron in the outer glass pane 22 may be selected for the outer glass pane 22. The thickness of the glass varies depending on the thickness selected. When iron is present in the glass, it exists in two oxidation states: Ferrous iron (Fe 2+ ) and ferric iron (Fe 3+ In one embodiment, Total iron may contain 20-30% ferrous iron, calculated as Fe2O3. Alternatively, the ferrous content can be determined by the amount of ferrous iron attributable to the iron. By measuring the absorption of glass at 1000 nm, which is in the region of the peak absorption Using the well-known Beer-Lambert law and the appropriate extinction coefficient for ferrous iron, It is possible to determine the ferrous content by using the ratio of ferrous to ferric in the glass. The method of optically determining the amount of color is described by C.R.Bamford in "Colour Cont 'Rol and Generation in Glass', Elsevier (19 77).
[0047] If the outer glass sheet 22 is thicker, the amount of Fe2O3 in the outer glass sheet 22 is In one embodiment, the outer glass sheet 22 is preferably thinner than the outer glass sheet 22. The glass plate 22 contains 0.8 to 2.0% by weight of Fe2O3 (total iron). In the present embodiment, the outer glass plate 22 contains 0.8 to 1.9% by weight of Fe2O3 (total iron). Preferably, the outer glass plate 22 contains 0.9 to 1.9% by weight of Fe2O3 (total iron). In some of these embodiments, the outer glass pane 22 comprises 0.9 to 1.8 wt. % In another embodiment, the outer glass sheet 22 has a Cr content of 0.9 to 1 0.4% by weight Fe2O3 (total iron). Thus, in certain embodiments, The composition of the side glass pane 22 has a higher iron content than the composition of the inner glass pane 16 .
[0048] In certain embodiments, it may be desirable for the window assembly 10 to exhibit certain color characteristics. In these embodiments, the outer glass sheet 22 may contain TiO2. If the outer glass pane 22 contains TiO2, the window assembly 10 will have the desired color characteristics. 1 shows a window assembly 10 that is capable of blocking ultraviolet light from entering the passenger compartment of a vehicle 12 through the window assembly 10. In one embodiment, the outer glass sheet 22 contains 0 to 1.25 wt. % TiO2. In another embodiment, the outer glass sheet 22 is made of 0.01 to 1.25% by weight of TiO2. In some embodiments, the outer glass sheet 22 contains 0 to 0.3 wt. % Ti. In one such embodiment, the outer glass pane 22 contains 0.01 to 0.3 In another embodiment, the outer glass sheet 22 contains 0.03 to 0. In another embodiment, the window assembly 10 includes a window having a thickness of 0.3 wt. The desired color and ultraviolet radiation blocking properties are achieved by adding CeO2 to the composition of the outer glass pane 22. In these embodiments, CeO2 is used as a substitute for TiO2. In one embodiment, the outer glass pane 2 2 contains 0 to 1.25 wt. % CeO2. In another embodiment, the outer glass plate 2 2 contains 0.01 to 0.5 wt% CeO2.
[0049] In one particular embodiment, the presence of Co3O4 in the outer glass pane 22 reduces visible light transmission. This is undesirable because it reduces the transmittance and affects the color of the outer glass pane 22. for the desired visible light transmittance and color characteristics of the window assembly 10 described below. It may be preferable that the composition of the glass plate 22 is substantially free of Co3O4. In the embodiments of the present invention, the phrase "substantially free of Co3O4" refers to the outer glass. This means that the plate 22 contains less than 10 parts per million (ppm) of Co3O4. In other embodiments, where a lower visible light transmission may be desirable, e.g., backlighting, rear side In a drylite, or rooflight, the outer glass panes are made of Co3O4, Se, and The colorant may be used to provide a suitable low visible light transmittance and transmission color to the glass sheet on the side of the glass. The composition may include other materials.
[0050] The window assembly 10 also includes a glass window disposed between the inner glass pane 16 and the outer glass pane 22. The polymer interlayer 28 is not limited to a particular thickness. However, in certain embodiments, the polymer intermediate layer 28 has a thickness of 0.3 to 1.8 mm. More preferably, the polymer intermediate layer 28 has a thickness of 0.5 to 1.6 mm. In one such embodiment, the polymer intermediate has a thickness of 0.6 to 0.9 mm. The thickness of layer 28 is 0.76 mm.
[0051] The polymer interlayer 28 may include a first major surface and a second major surface. In an embodiment, the interlayer 28 is configured to conform to the shape of the inner glass sheet 16 and the outer glass sheet 22. As shown in FIG. The first and second major surfaces of the polymer interlayer 28 are provided in parallel relationship to one another. In other embodiments, such as those in which the window assembly 10 can be used in a head-up display application, In some cases, such as when used in a thermally-insulated housing, the first and second major surfaces of the polymer intermediate layer 28 are In these embodiments, the polymer intermediate layer 28 may not be provided in a parallel relationship. The first major surface or the second major surface may be arranged such that one surface is disposed at an angle to the other. In another embodiment, the polymer intermediate layer 28 may be arranged in a generally triangular or helical shape. It may also be in the form of a .
[0052] Preferably, the polymer interlayer 28 is transparent and substantially transmissive to visible light. Optionally, the polymer interlayer 28 is tinted to provide additional solar control functionality. , and / or an IR reflective film. However, the advantage of the window assembly 10 is , without being tinted or requiring IR reflective films, characteristics and visible light transmittance, which can be compared to prior art designs. This reduces the cost of the window assembly 10. The polymer interlayer 28 may be, for example, a polyvinyl chloride. Suitable polymers such as polyvinyl chloride (PVB), or PVC, EVA and polyurethanes. It may be or include another suitable material.
[0053] The polymer interlayer may have improved sound reducing properties, for example, the polymer interlayer may , may include an acoustically modulating PVB.
[0054] To form the window assembly 10, the inner glass sheet 16 and the outer glass sheet 22 are They may be laminated together or otherwise bonded together via a polymer interlayer 28. Lamination processes known in the art may include laminating the polymer through a polymer interlayer 28. 2 to bond the inner glass pane 16 to the outer glass pane 22 to form the window assembly 10. Typically, such a lamination process involves laminating an inner glass sheet 16 and an outer glass sheet A polymer interlayer 28 is inserted between the plate 22 and the intermediate layer and plate are heated at a predetermined temperature and pressure. to form the laminated window assembly 10.
[0055] Once the window assembly 10 is formed, the window assembly 10 has a thickness of less than 5.0 mm. In one particular embodiment, the thickness of the window assembly 10 is preferably 4.0 mm. In other embodiments, the thickness of the window assembly 10 may be less than 3.0 mm. In these embodiments, the window assembly may be at least 2.0 mm thick. It may have a thickness.
[0056] The transmitted color exhibited by the window assembly 10 is an advantageous feature. For purposes of describing the embodiment, the transmitted color exhibited by the window assembly is the color of the assembly Refers to the visible light transmitted through a window assembly measured at a 90 degree angle incident from the illuminant D 65, explained in relation to the CIELAB color scale system using a 10 degree observer. Preferably, the window assembly 10 exhibits a green transmission color. The window assembly 10 is oriented in accordance with the CIELAB color scale system (illuminant D65, 10 degrees In some embodiments, the window assembly exhibits an a* value of -12 to -5 according to a human observer. The 10th generation follows the CIELAB color scale system (illuminant D65, 10 degree observer). The window assembly 10 also exhibits an a* value of -12 to -6, preferably -11 to -6. In transmission using the CIELAB color scale system (illuminant D65, 10 degree observer) In certain embodiments, the window assembly 10 may exhibit a b* value of -2 to 6. In these embodiments, the window assembly 10 has a CIELAB color. In transmission according to the color scale system (illuminant D65, 10 degree observer), the preferred The lightness (L*) exhibited by the window assembly is determined by the light intensity (b*) of the window. Explained in relation to the CIELAB color scale system using illuminant D65 and a 10 degree observer. The window assembly 10 is adapted to display the CIELAB color scale system (illuminant D65, It is preferable that the luminance exhibits an L* of 88 or more at a 10 degree observer.
[0057] The window assembly 10 also exhibits other advantageous characteristics. For example, the window assembly 10 has a low As used herein, direct solar transmittance (TDS) refers to According to the relative solar radiation spectrum distribution of air mass 1.5, in the wavelength range of 300 to 2500 nm The direct solar transmittance is calculated based on the ISO13837:2008 standard. The window assembly may be determined according to a recognized standard, such as approximately A. In one such embodiment, the window 10 exhibits a direct solar transmittance of 55% or less. The assembly 10 may exhibit a direct solar transmittance of 40-55%. In this case, the window assembly 10 exhibits a direct solar transmittance of 52% or less. The assembly 10 exhibits a direct solar transmittance of 50% or less. The assembly 10 may exhibit a direct solar transmittance of 45% or less. Thus, the window assembly 10 may exhibit a direct solar transmittance of at least 40%.
[0058] The window assembly 10 may exhibit low total solar transmittance. The total transmittance (TTS) is the ratio of the solar energy that passes directly through a window assembly to the solar energy that is absorbed by the assembly. This includes the solar energy absorbed by the atmosphere, which is then convected and dissipated inwards, resulting in a mass of air of 1 Integral over the wavelength range of 300-2500 nm according to the relative solar radiation spectral distribution of .5 Total solar transmittance is measured according to recognized standards such as ISO13837:2008 Standard A. In one particular embodiment, the window assembly may be determined at a wind speed of 14 kilometers per hour. The assembly 10 exhibits a total solar transmittance of 65% or less. The assembly 10 exhibits a total solar transmittance of 55 to 65%. The window assembly 10 exhibits a total solar transmittance of 62% or less. In these embodiments, the window assembly 10 exhibits a total solar transmittance of at least Both may exhibit a total solar transmittance of 55%.
[0059] Embodiments of the window assembly 10 may also exhibit advantageous total visible light transmittance. When assembly 10 is utilized as a window pane in vehicle 12, the assembly 10 is The total visible light transmittance achieved is achieved by providing a reasonable amount of visible light transmittance to the passenger compartment of the vehicle 12. For purposes of describing the window assembly 10, a total visible light transmission is used. The ratios are related to the CIELAB color scale system using illuminant A and a 2 degree observer. , refers to the percentage of visible light that passes through the assembly measured from the side facing the inner glass sheet. In the embodiment described above, the window assembly 10 is a CIELAB color scale system ( It is preferable that the total visible light transmittance is 70% or more when viewed from a 2-degree observer. In certain embodiments, the window assembly 10 is adapted to display the CIELAB color scale system. (illuminant A, 2-degree observer) has a total visible light transmittance of 75% or more. In an embodiment, the window assembly 10 is reflective of the CIELAB color scale system (Illuminant A It has a total visible light transmittance of 70-80% at 2-degree observer. Depending on the application or location of the window assembly 10 in the window assembly 10, the window assembly 10 may have a thickness of less than 70%. For example, if the window assembly 10 is a backlight, a rear side When utilized as a light or roof light, the window assembly 10 may be <70% total visible light transmittance in color scale system (illuminant A, 2 degree observer) In some of these embodiments, the window assembly 10 may include a CIEL Total visible light transmittance less than 50% in the AB color scale system (illuminant A, 2 degree observer) Preferably, the window assembly 10 is backlit or has a rear side light. When utilized as a light, the window assembly 10 is compatible with the CIELAB color scale system. (Light source A, 2 degree observer) may exhibit a total visible light transmittance of 30% or less. When the window assembly 10 is utilized as a rooflight, the window assembly 10 is less than 20% in the RGB scale system (illuminant A, 2 degree observer), preferably 1 It may exhibit a total visible light transmittance of 0% or less. EXAMPLES
[0060] The following examples are presented only to further illustrate and disclose embodiments of window assemblies. The window assembly examples described below (Examples 1-3) are prophetic. and exhibits the characteristics listed in the table.
[0061] The window assemblies of Examples 1 to 3 each include an inner glass sheet. The inner glass pane has the soda-lime-silica composition as above and a thickness of 0.5 mm. In Examples 2 and 3, the inner glass panes were made of soda lime silicate glass similar to that described above. In Examples 1 to 3, the inner glass plate has a composition of 0.1 mm and a thickness of 0.7 mm. It is transparent and may be formed by the float glass manufacturing process or another process The glass sheets used for each inner plate are fused using the molten salts mentioned above. be academically enhanced.
[0062] A tinted outer glass plate was also provided for each of Examples 1 to 3. The plates had a soda-lime-silica composition. In Example 1, the composition was 72% by weight of Si O2, 3.9 wt% MgO, 7.0 wt% CaO, 14 wt% Na2O, 0.5 wt% % K2O, 7.5% CaO, and 1.1% Al2O3 by weight. In Examples 2 and 3, the composition was 72 wt. % SiO2, 3.9 wt. % MgO. , 7.5 wt% CaO, 14 wt% Na2O, 0.5 wt% K2O, 7.5 wt% In Example 1, the outer glass The plates also contained 1.8 wt. % Fe2O3 (total iron). In Example 2, the outer glass plates 1.3 wt.% Fe2O3 (total iron). In Example 3, the outer glass panes contained 1. 3% by weight of Fe2O3 (total iron). In Examples 1 to 3, the total iron was Fe2O For the avoidance of doubt, the total iron content of the outer plate was calculated as 28% of the ferrous iron content. The ferrous content is 28% and the amount of Fe2O3 is calculated as Fe2O3, which is 1.3% by weight. In Example 3, where 3, the ferrous content expressed as Fe2O3 is (=1.3 x 28 / 100 ) at 0.364% by weight.
[0063] The outer plate of Example 1 has a thickness of 1.3 mm, and the outer plate of Example 2 has a thickness of 1.8 mm. The outer pane of Example 3 has a thickness of 2.1 mm. The panes are formed by the float glass manufacturing process, each of which is made as a sheet of glass. Provided.
[0064] Each outer glass pane is bonded to the inner pane using the transparent polymer interlayer described above. In each of Examples 1 to 3, the intermediate layer is a PVB composition and has a thickness of It had a thickness of 0.76 mm and was substantially transparent to visible light.
[0065] Total visible light transmittance (Tvis), transmitted color (Ta*, Tb*), lightness (L*), direct solar energy transmittance (TDS), and total solar transmittance ( The total visible transmittance (TTS) is reported in the table. For each example, the total visible transmittance was calculated based on optical modeling. Therefore, according to the CIELAB color scale system using illuminant A and a 2 degree observer The transmitted color and brightness reported in the table were calculated by optical modeling. Calculated according to the CIELAB color scale system using D65, 10 degree observer Direct solar transmittance was calculated by optical modeling and conforms to ISO13837:2008 The total solar transmittance was determined according to Regulation A. The total solar transmittance was calculated by optical modeling and conforms to ISO 13837:2008 Regulation A was determined at a wind speed of 14 kilometers per hour. Total visible light transmittance, direct solar transmittance, and total solar transmittance are reported as percentages. It is expressed as: [Table 1]
[0066] As shown in the table, the window assembly embodiments shown in Examples 1 to 3 are -1 according to the ELAB color scale system (illuminant D65, 10 degree observer) It has an a* value of 2 to -5 and an ab* value of 2 to 6, so it has a green-yellow transmission color. The window assemblies shown in Examples 1 to 3 exhibit high visible light transmittance. The window assemblies of Examples 1 to 3 each exhibit a visible light transmittance of 70% or more ( Illuminant A, 2 degree observer). In fact, the window assemblies of Examples 1 and 2 were 7 The visible light transmittance is 5% or more (illuminant A, 2-degree observer). The window assembly exhibits a direct solar radiation transmittance of less than 55%. The window assemblies exhibit a direct solar transmittance of less than 50%. The assembly exhibits a total solar transmittance of less than 65%. Additionally, the window assembly of Example 3 has It showed a total solar transmittance of less than 60%.
[0067] Accordingly, the present invention provides a window assembly including a first glass pane. The plate is chemically strengthened and exhibits a surface compressive stress of more than 400 MPa. The glass sheet has a first major surface and a second major surface. The first main surfaces of the glass plates are opposed to each other. The second glass plate is made of 68 to 74% by weight of SiO 2, 2-6% by weight MgO, 1-10% by weight CaO, 12-16% by weight Na2O, 0 ~1 wt% K2O, 0.8-2.0 wt% Fe2O3 (total iron), 0-1.25 wt% The polymer intermediate layer comprises 0 to 1.25 wt. % of TiO2 and 0 to 1.25 wt. % of CeO2. The window assembly has a direct solar transmittance of 55% or less. It has a solar transmittance of 65% or less.
[0068] Various modifications, additions, and additions may be made to the above detailed description without departing from the true scope and spirit of the present invention. It will be apparent that other alternative embodiments are possible. The embodiments have been chosen and are intended to provide the best illustration of the principles of the invention and its practical application. The description will enable one skilled in the art to adapt the invention to various configurations suitable for the particular application contemplated. It will be understood that the present invention may be practiced in various embodiments and with various modifications. and all such modifications and variations are intended to be within the scope of the present invention.
Claims
1. a first glass sheet (16) that is chemically strengthened and exhibits a surface compressive stress of 400 MPa or more; A second glass sheet (22) having a first main surface (24) and a second main surface (26), the second main surface (26) of the second glass sheet (22) and the first main surface (18) of the first glass sheet (16) being opposed to each other, the second glass sheet (22) being made of 68 to 74% by weight of SiO 2 , 2 to 6 wt.% MgO, 1 to 10 wt.% CaO, 12 to 16 wt.% Na 2 O, 0 to 1% by weight of K 2 O, 0.8 to 2.0 wt.% Fe 2 O 3 (total iron), 0 to 1.25 wt.% TiO 2 %, and 0 to 1.25 wt. % CeO 2 A second glass sheet (22) comprising: 2 O 3 A second glass sheet (22) which is ferrous, calculated as a polymer interlayer (28) disposed between the first glass sheet (16) and the second glass sheet (22), a direct solar transmittance integrated over the wavelength range 300-2500 nm according to a relative solar spectral distribution of 55% or less of an air mass of 1.5, and a total solar transmittance integrated over the wavelength range 300-2500 nm according to a relative solar spectral distribution of 65% or less of an air mass of 1.5; The thickness of the second glass sheet (22) is greater than the thickness of the first glass sheet (16); The thickness of the second glass plate (22) is 4 mm or less, and the thickness of the first glass plate (16) is 2 mm or less, The thickness of the window assembly (10) is between 2.0 and 5.0 mm; The first glass sheet (16) is 66 to 72% by weight of SiO 2 , 8 to 15 wt.% MgO, 1 to 8 wt.% CaO, 12 to 16 wt.% Na 2 O, 0 to 1% by weight of K 2 O, and 1.0 to 5.0 wt. % Al 2 O 3 or the first glass sheet (16) comprises 58 to 70% by weight of SiO 2 , 4 to 10 wt. % MgO, 0 to 1 wt. % CaO, 12 to 18 wt. % Na 2 O, 0.1 to 5% by weight of K 2 O, and 5 to 15 wt. % Al 2 O 3 and having an ion penetration depth of 200 microns or greater.
2. 10. The window assembly of claim 1, exhibiting a total visible light transmission (Illuminant A, 2 degree observer) of 70% or greater, measured from the side facing the first glass sheet.
3. 3. The window assembly of claim 1 or claim 2, wherein the transmitted color (illuminant D65, 10 degree observer) exhibited by said window assembly (10) is green-yellow.
4. 4. A window assembly according to any one of the preceding claims, wherein the transmitted colour (illuminant D65, 10 degree observer) exhibited by said window assembly (10) has an a* value of -12 to -5 and a b* value of 0 to 6.
5. The second glass sheet (22) is 0.8 to 1.9 wt. % Fe 2 O 3 5. A window assembly according to any one of claims 1 to 4, comprising (all iron).
6. The second glass sheet (22) contains 0.9 to 1.9% by weight of Fe. 2 O 3 6. A window assembly according to any preceding claim, comprising (all iron).
7. The second glass sheet (22) contains 0.9 to 1.4 wt. % Fe 2 O 3 7. A window assembly according to any preceding claim, comprising (all iron).
8. 2. The window assembly of claim 1, wherein the thickness of the second glass sheet (22) is at least 1.5 times greater than the thickness of the first glass sheet (16).
9. The second glass sheet (22) contains 0.01 to 0.3 wt. % TiO 2 9. A window assembly according to any one of claims 1 to 8, comprising:
10. The second glass sheet (22) is substantially 3 O 4 10. A window assembly according to any one of the preceding claims, which does not comprise
11. Al in the second glass sheet (22) 2 O 3 A window assembly according to any one of the preceding claims, wherein the weight percentage of Al2O3 in the first glass sheet (16) is less than the weight percentage of Al2O3 in the first glass sheet (16).
12. The second glass sheet (22) is made of 0 to 2% by weight of Al. 2 O 3 12. A window assembly according to any one of the preceding claims, comprising:
13. The first glass sheet (16) is 66 to 72% by weight of SiO 2 , 8 to 15 wt.% MgO, 1 to 8 wt.% CaO, 12 to 16 wt.% Na 2 O, 0 to 1% by weight of K 2 O, and 4.0 to 5.0 wt. % Al 2 O 3 The window assembly of claim 1 , comprising:
14. A window assembly according to any one of the preceding claims, wherein the first glass sheet (16) exhibits a surface compressive stress of at least 450 MPa.
15. 15. The window assembly of claim 14, wherein the first glass sheet (16) exhibits a surface compressive stress of 600 MPa or greater.
16. 16. A window assembly according to claim 14 or claim 15, wherein the first glass sheet (16) exhibits a surface compressive stress of between 600 and 1,000 MPa.
17. Window assembly according to any one of the preceding claims, wherein the first glass pane (16) is an inner glass pane and the second glass pane (22) is an outer glass pane.
18. 18. A window assembly according to any one of the preceding claims, wherein the first glass pane (16) is a sheet of float glass and the second glass pane (22) is a sheet of float glass.
19. 19. The window assembly according to any one of the preceding claims, wherein the window assembly (10) exhibits a direct solar transmittance of no greater than 52% and a total solar transmittance of no greater than 62%.
20. The window assembly according to any one of the preceding claims, wherein the window assembly (10) exhibits a direct solar transmittance of between 40 and 55%.
21. 21. The window assembly according to any one of the preceding claims, wherein the window assembly (10) exhibits a total solar transmittance of 55 to 65%.
Citation Information
Patent Citations
Ultraviolet and infrared absorption colored glass plate
JP2004123495A
Chemically temperable glass sheet
WO2016169823A1
Asymmetric laminated glass
WO2017103471A1